Museum interaction experience, visitor satisfaction and behavior intentions: a case of national museum / Nurul Nadiah Basiran - Basiran, Nurul Nadiah (2013)
Cultural and heritage tourism is one of the major sectors of the tourism industry, where many countries use this segment as their tourism strategy in boost tourism sector in a particular destination. Globally, the museum plays an important role in heritage tourism. Malaysia offer diverse and unique heritage in culture where National Museum had preserved all these traditional oral history and knowledge for the future generations. Therefore it is becoming more essential for museum institution to recognize important attributes to enhance the function of museum globally. The purpose of this study was to identify on the attributes that influence visitors’ satisfaction on National Museum that could lead to behavioral intentions. The literature review presented a brief overview on heritage tourism, museum interaction experience, visitor satisfaction and behavior intention. The findings look forward on the behaviour intention of the visitors after the experience the museum interaction attributes and find out what elements important in museum performance.